2000
DOI: 10.1007/bf03018978
|View full text |Cite
|
Sign up to set email alerts
|

Does intrathecal morphine alter the stress response following coronary artery bypass grafting surgery?

Abstract: 463CAN J ANESTH 2000 / 47: 5 / pp [463][464][465][466] Purpose: Intrathecal morphine administered prior to coronary artery revascularization (CABG) surgery was studied to determine its effects on the stress response.Methods: In a single centre, open, randomized clinical trial, first time elective CABG surgery patients, < 75 yr, were studied. Control subjects (n=12) received a standardized anesthetic consisting of fentanyl (maximum cumulative dose of 35 µg·kg -1 ), propofol, and pancuronium. In addition, spinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 14 publications
1
7
0
2
Order By: Relevance
“…In our study using 500 μg intrathecal morphine, the extubation times were similar in both groups. Definition of stricter criteria for extubation might have allowed shorter extubation, as reported by others [27–35]. However, more episodes of respiratory depression occurred in the control group.…”
Section: Discussionmentioning
confidence: 62%
“…In our study using 500 μg intrathecal morphine, the extubation times were similar in both groups. Definition of stricter criteria for extubation might have allowed shorter extubation, as reported by others [27–35]. However, more episodes of respiratory depression occurred in the control group.…”
Section: Discussionmentioning
confidence: 62%
“…The use of intrathecal opioids in paediatric cardiac surgery has been limited due to the fact that children with congenital heart disease often have other complex conditions and concerns exist regarding the risk of haematoma-induced spinal cord compression. None of the previous studies investigating the use of ITM for cardiac surgery (5,6,8,(14)(15)(16), including data in 3400 and 1000 patients (14,15), respectively, report development of subarachnoid or epidural haematomas. As a precaution it has been suggested that the time from lumbar puncture to systemic anticoagulation with heparin must exceed 60 min (17), and in this study the mean time period was 102 min (range 55-235 min).…”
Section: Discussionmentioning
confidence: 99%
“…In adult cardiovascular surgical patients, intrathecal morphine has been shown to be a safe method of pain control producing significant analgesia and partially attenuating the post-surgical stress response (5,6). There are few reports of the use of intrathecal morphine in children (ITM) (1,(7)(8)(9)(10)(11) and only two studies concerning pediatric cardiac surgery in children (8,9).…”
mentioning
confidence: 99%
“…Im Rahmen operativer Eingriffe tragen Schmerz und Angst, aber auch Trigger, wie Trauma, Hypovolämie oder Azidose, ebenfalls zu einer Aktivierung der hypothalamo-hypophysär-adrenalen Achse mit einem Konzentrationsanstieg von Katecholaminen und Nebennierenrindenhormonen im Plasma bei. Die Freisetzung von Noradrenalin, Adrenalin oder Kortisol kann spezifische und unspezifische Abwehrmechanismen in Stresssituationen beeinträchti-gen und die immunsuppressiven Effekte des Morphins verstärken.Auch in klinischen Studien an herzchirurgischen Patienten konnte durch eine intrathekale Gabe von Morphin zwar eine suffiziente Analgesie, nicht jedoch eine zuverlässige Hemmung der perioperativen Stressantwort erzielt werden [16,35].…”
Section: Opioid-induzierte Immunsuppressionunclassified
“…Dabei wirkt sich insbesondere die epidurale bzw. intrathekale Gabe von Morphin vorteilhaft aus [15,35]. Über einen negativen Feedback-Mechanismus via Hypothalamus-Hypophyse-Nebenniere kann somit der direkte inhibierende Effekt von Morphin auf das Immunsystem durch eine Abschwächung der perioperativen Stressantwort verstärkt werden.…”
Section: Anästhesieunclassified